Household economic burden and catastrophic expenditures in non-resistant tuberculosis patients: cross-sectional survey in Guizhou, China - Ma, Xiaoxue; Huang, Aijue; Chen, Huijuan; Zhou, Jian; He, Yuying; Wang, Weibing; Du, Rong; Guo, Xueli; Zhao, Qi; Li, Jinlan (Frontiers in Public Health, 2025)
ObjectivesIn accordance with the World Health Organization (WHO)'s “End TB Strategy,” which aims to eradicate catastrophic expenditures faced by TB-affected families, we intend to thoroughly investigate and comprehend the economic burden, catastrophic expenditures, and contributing factors pertaining to non-drug-resistant tuberculosis patients’ families in Guizhou Province. Our goal is to formulate policy recommendations that can effectively alleviate the financial strain on these patients and their families.MethodsThe pulmonary tuberculosis cases, which were non-drug-resistant, registered across the province during May–June 2020, and successfully treated at the time of the survey, underwent questionnaire interviews conducted through probability proportional sampling. Utilizing the WHO methodology, the household economic burden borne by these patients was computed, with the mean and median (interquartile range), abbreviated as “M (IQR),” employed to describe the economic burden, and the proportion (%) used to depict catastrophic expenditures. Further analysis of the factors influencing catastrophic expenditures within these families was conducted using chi-squared (χ2) tests and binary logistic regression.ResultsThe average total out-of-pocket expenses (OOP) incurred by 2,283 non-drug-resistant pulmonary tuberculosis patients in Guizhou Province amounted to 10,581.82 RMB (1453.11), with a median expenditure of 5,277 RMB (IQR: 2,110–12,352 RMB). Notably, indirect expenses comprised 58.07% of the total expenditure. Taking the time of diagnosis as the cut-off point, the majority of these expenses occurred during the treatment phase, but the before diagnosis stage also imposed a significant economic burden, averaging 3,191.58 RMB (438.27). Among the 2,283 patients, 50.37% (1,150 patients) experienced catastrophic events due to their medical expenses. Key risk factors for these catastrophic events included poverty, employment status, before diagnosis visits, hospitalization, mobility issues, and delayed diagnosis.ConclusionThe economic burden imposed on households by tuberculosis patients in the province remains considerable, with the indirect burden accounting for the lion’s share. The likelihood of catastrophic expenditures persists, significantly influenced by factors such as poverty, hospitalization, delayed diagnoses, and before diagnosis visits. Recommendations include reinforcing targeted public health education, enhancing the diagnostic and therapeutic capabilities of medical institutions, regulating their practices, curbing unnecessary hospitalizations, and instituting a long-term framework aimed at alleviating the indirect economic burden. By doing so, we can collaboratively diminish the economic strain on patients and mitigate the risk of catastrophic expenditures, ultimately striving for the achievement of zero catastrophic expenditures among households.